Cross-cultural adaptation and validation of the Hebrew version of the medial tibial stress syndrome score among active-duty servicemembers. - Klein, Roei; Elboim-Gabyzon, Michal; Rozenfeld, Evgeni; Kalichman, Leonid (Physiotherapy Theory & Practice, 2026)
Background: Medial tibial stress syndrome (MTSS) affects up to 35% of military recruits during basic training, yet no validated patient-reported outcome measure (PROM) exists to assess this condition in Hebrew-speaking populations. The MTSS score is a validated PROM for assessing symptom severity; however, it requires linguistic adaptation for use among Hebrew-speaking individuals. Objective: To translate and assess psychometric properties of the Hebrew version of the Medial Tibial Stress Syndrome score (MTSS-He) among active-duty servicemembers. Methods: Following Beaton's guidelines, the MTSS score was translated into Hebrew and culturally adapted. A total of 133 participants were recruited. A cross-sectional validation study was conducted with 72 active-duty servicemembers diagnosed with MTSS (mean age 19.32 ± 0.8 years, 63.9% male). Psychometric properties, including internal consistency (Cronbach's Alpha (α) and McDonald's Omega (ω)), test-retest reliability (ICC3,1), concurrent validity (Spearman correlations with Short Form 12 and numerical pain rating scales), and discriminative validity were assessed. Results: The MTSS-He demonstrated acceptable internal consistency (α = 0.66, ω = 0.68), good test-retest reliability (ICC3,1 = 0.75), and significant correlations with pain measures (rho = 0.32–0.61, p <.01). The instrument significantly discriminated between patients with MTSS and asymptomatic controls (p <.001), with median MTSS-He scores of 3 (IQR: 2–4). Conclusions: The MTSS-He is a reliable and valid instrument for assessing MTSS in Hebrew-speaking active-duty servicemembers, addressing a critical gap in Hebrew-language assessment tools. It enables standardized symptom quantification and outcome comparison, with potential for broader application in clinical and research settings. Future studies should investigate structural validity based on internal consistency test results and extend validation to civilian and athletic populations.